Oral manifestations in hospital-admitted COVID-19 patients: a case control study - Alhamed, Sana; Aljohani, Suad (Frontiers in Oral Health, 2023)
The oral cavity can present early manifestations of several systemic diseases. Since 14 the emergence of the COVID-19 pandemic, there have been many published studies 15 reporting the direct effect of the virus on the orofacial structures. Here, oral signs and 16 symptoms of 22 hospital admitted COVID-19 patients were examined and compared 17 to a matching control group. Loss of taste and smell was the most prevalent symptom 18 (65%), followed by oral dryness (45%) and halitosis (30%). The most common oral 19 lesions were candidal infection (68%). Other less common manifestations were oral 20 ulcerations (36%) followed by white patches (27.3%). There was a statistically 21 significant association between candidal infection and age of the study group, where 22 the p-value is 0.008. Here, 80% of those who had candida infection are aged 60 years 23 and more. There was no significant association with comorbidities such as diabetes 24 mellitus and hypertension.